A review of studies on sustainable development in mining life cycle. (20th August 2019) - Asr, Elmira Tajvidi; Kakaie, Reza; Ataei, Mohammad; Tavakoli Mohammadi, Mohammad Reza
Abstract: Mining industry is closely linked with sustainable development, which leads to positive and negative impacts of this industry on three key principles of sustainable development, including society, economy, and environment. For ideal implementation and integration of sustainable development in the industry, the three principles of sustainability should be simultaneously applied and not sequentially at different stages of the mining life cycle to maximize the opportunities in the mining industry to contribute to comprehensive development. A suitable framework for sustainable development will be created through the interaction of these principles with activities carried out in different stages of mining life cycle and their implementation in the mining projects can be economically profitable, environmentally clean, and socially responsible. In this study, the researchers' comments about the sustainability or unsustainability of the mining industry have been presented, as well as the necessity of integrating sustainable development considerations in mining life cycle, expression of sustainability conditions, necessary measures, and appropriate solutions for each stage. Also, the review of the studies will be discussed. Graphical abstract: Image 1040513